2011
DOI: 10.1039/c0jm04331a
|View full text |Cite
|
Sign up to set email alerts
|

Graphene sheets decorated with SnO2 nanoparticles: in situ synthesis and highly efficient materials for cataluminescence gas sensors

Abstract: Graphene sheets decorated with SnO 2 nanoparticles were prepared through a facile hydrothermalassisted in situ synthesis route. According to the XPS, XRD, FESEM and TEM analysis, rutile SnO 2 nanocrystals were exclusively deposited on graphene sheets with high density and high uniformity to form layered composite sheets. Propanal, a common volatile organic compound, was selected as a model to investigate the cataluminescence (CTL) sensing properties of the SnO 2 /graphene composite in this paper. It was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 293 publications
(140 citation statements)
references
References 45 publications
7
133
0
Order By: Relevance
“…Graphene and graphene derivatives (e.g., graphene/graphite oxide, functionalized graphene, etc.) could be used in various applications such as hydrogen storage [82], sensors [83], transparent conductive films [84], batteries [85,86], super capacitors [87], solar cells [88] and nanocomposites coatings [89][90][91]. Due to the high surface area of graphene sheet (2630 m 2 /g), improvement of mechanical, thermal, and electrical properties of composite graphene based coating could be achieved with very low loading [92].…”
Section: Graphene As Green Corrosion Inhibitor In Anticorrosion Coatingmentioning
confidence: 99%
“…Graphene and graphene derivatives (e.g., graphene/graphite oxide, functionalized graphene, etc.) could be used in various applications such as hydrogen storage [82], sensors [83], transparent conductive films [84], batteries [85,86], super capacitors [87], solar cells [88] and nanocomposites coatings [89][90][91]. Due to the high surface area of graphene sheet (2630 m 2 /g), improvement of mechanical, thermal, and electrical properties of composite graphene based coating could be achieved with very low loading [92].…”
Section: Graphene As Green Corrosion Inhibitor In Anticorrosion Coatingmentioning
confidence: 99%
“…500 A HRG/SnO 2 based gas sensor showed good sensitivity towards propanol, an important volatile aldehyde used in chemical and medical industries. 501 Sensors based on HRG/SnO 2 nanocomposites were applied for the detection of H 2 S, NH 3 , and NO 2 . 502,503…”
Section: Chemical Sensorsmentioning
confidence: 99%
“…Considering the CL spectra and the fluorescence spectra of YVO 4 : Eu 3+ nanocrystals, an energy transfer mechanism from excited intermediates to the YVO 4 : Eu 3+ nanocrystals was proposed. Recently, Song et al [67] have reported hydrothermal-assisted in situ synthesis of graphene sheets decorated with SnO 2 nanoparticles. Strong CTL emission of propanal on the surface of SnO 2 /graphene composite was found; and this composite was engineered as an efficient, highly sensitive and selective sensor for propanal.…”
Section: Sensorsmentioning
confidence: 99%